Physical, Microbial, and Chemical Quality of Hot-Air-Dried Persimmon (Diospyros kaki) Chips during Storage - Rebecca R. Milczarek; Ana M. Vilches; Carl W. Olsen; Andrew P. Breksa; Bruce E. Mackey; Maria T. Brandl (Journal of Food Quality)
Recent efforts have been made to develop hot-air-dried chips as a value-added product for persimmon fruit (Diospyros kaki). However, the long-term quality of this product and its dependence on processing conditions and packaging type have not yet been explored. Hence, in this work, chips were prepared from “Hachiya” persimmon fruit in 2 ways: 2 mm thickness fruit slices, hot-air-dried for 5 hours (Preparation 2–5), and 6 mm slices, dried for 10 hours (Preparation 6–10). The dried chips were then packaged into 2 bag types (plastic zip-top and metallized polyethylene terephthalate (Met-PET) with desiccant packets), stored under ambient conditions, and sampled for moisture-related, microbial, texture, and chemical quality traits throughout the 1-year storage study. It was found that–with the exception of a marked decrease in ascorbic acid (vitamin C)—all 4 Preparation/Packaging combinations yielded products that maintained acceptable color, microbial, nutritional, and textural quality throughout the entire study. Compared to Preparation 2–5 chips, Preparation 6–10 chips generally had lower contents of healthy nutrients—antioxidant compounds, ascorbic acid, and carotenoids. Evidence of invertase activity was found for Preparation 6–10 chips but not for Preparation 2–5 chips. For both preparations, the contents of ascorbic acid and carotenoids experienced time-dependent decreases. Plastic zip-top bags and Met-PET bags with desiccant packets performed equally well as packaging for most of the quality metrics tracked during this study. Overall, this work has demonstrated that hot-air-drying of persimmon slices is a promising approach to create a value-added product with at least one year of shelf-life.